Seroprevalence of Pteropine orthoreovirus in humans remain similar after nearly two decades (2001–2002 vs. 2017) in Tioman Island, Malaysia - Wai J. Leong; Xin F. Quek; Hui Y. Tan; Kim M. Wong; Hariz S. Muhammad; Siew T. Wong; Mohd L. Abdullah; Pooi P. Leong; Linfa Wang; Kenny Voon; Nurul Azmawati Mohamed @ Abd Aziz (Wiley Periodicals LLC, 2024)
Indexed by WOS/SCOPUS/ERA